The Really Real, Authentic, Original Shakespeare - Kostihova, Marcela (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
This essay considers the question of how original/new interpretations help redefine (or reify) the original/old perception of Shakespeare and the work its cultural capital performs, demonstrating the inherent impossibility of reconciling an “original” Shakespeare with contemporary performances of his plays through a reading of Twelfth Night, and address some of the ideological implications of trying to conflate the two. It then takes a detour into contemporary marketing and consumer-psychology literature to explore the crucial roles which the concepts of “authenticity” and “originality” have come to play in contemporary consumer culture, circling back to Shakespeare, to ruminate on the implications of the use of his cultural capital as an ultimate positional good in the 21st century.